Enterococcus faecium PBP5-S/R, the Missing Link between PBP5-S and PBP5-R - Pietta, Ester (Antimicrob Agents Chemother, 2014)
During a study to investigate the evolution of ampicillin resistance in Enterococcus faecium, we observed that a number of E. faecium strains, mainly from the recently described subclade A2, showed PBP5 sequences in between PBP5-S and PBP5-R. These hybrid PBP5-S/R patterns reveal a progression of amino acid changes from the S form to the R form of this protein; however, these changes do not strictly correlate with changes in ampicillin MICs.